Cameras in the Countryside: Recreational Photography in Rural Ontario, 1851-1920 - McIsaac, Jacqueline (Scientia Canadensis, 2013)
The introduction and subsequent refinement of glass plate negative technology facilitated photography’s appropriation within rural Ontario. As a recreational consumer technology, the camera became easier to use, financially accessible, and portable, thus better suiting the needs of rural consumers. While technological advancements allowed the camera to be adopted as a leisure pursuit, its use was directed by the countryside’s cultural values and social norms. These interests influenced who used cameras, how photo-supplies were purchased, the camera’s place within household income diversification strategies, and the photographer’s gaze, all of which suggest that when photo-technology was used in the countryside, it was as an extension of, not a challenge to, rural cultural values. At the same time, as the first photography system that was accessible to the middle and labouring classes, glass plates cannot help but reveal the visual priorities this new group of consumers, thus contributing to current discussions on cultural aspects of rural society. Consequently, glass plate cameras in Ontario’s countryside functioned as both a documentary medium as well as a form of cultural expression.